2016
DOI: 10.1016/j.bbi.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced neuroinflammation is mediated by GSK3-dependent TLR4 signaling that promotes susceptibility to depression-like behavior

Abstract: Most psychiatric and neurological diseases are exacerbated by stress. Because this may partially result from stress-induced inflammation, we examined factors involved in this stress response. After a paradigm of inescapable foot shock stress that causes learned helplessness depression-like behavior, eighteen cytokines and chemokines increased in mouse hippocampus, peaking 6 to 12 hr after stress. A 24 hr prior pre-conditioning stress accelerated the rate of stress-induced hippocampal cytokine and chemokine inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 102 publications
2
95
0
5
Order By: Relevance
“…Recently it was found that psychological stress-induced activation of GSK3 is intimately linked to inflammation, as blocking signaling through TLR4 blocked the activation of GSK3 by stress. Blocking this signaling through TLR4 and GSK3 also decreased stress-induced inflammation, and nearly eliminated the development of depressive symptoms in mice [15]. Thus, susceptibility to depressive characteristics in rodents, and perhaps depression in humans, is promoted by psychological stress-induced signaling through TLR4 that activates GSK3 and neuroinflammation.…”
Section: Glycogen Synthase Kinase-3 (Gsk3) Is Activated By Stress Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it was found that psychological stress-induced activation of GSK3 is intimately linked to inflammation, as blocking signaling through TLR4 blocked the activation of GSK3 by stress. Blocking this signaling through TLR4 and GSK3 also decreased stress-induced inflammation, and nearly eliminated the development of depressive symptoms in mice [15]. Thus, susceptibility to depressive characteristics in rodents, and perhaps depression in humans, is promoted by psychological stress-induced signaling through TLR4 that activates GSK3 and neuroinflammation.…”
Section: Glycogen Synthase Kinase-3 (Gsk3) Is Activated By Stress Andmentioning
confidence: 99%
“…In the brain, the cytosolic inflammasome complex containing NLRP3 has particularly received attention because it is activated in microglia, macrophages and astrocytes in response to psychological stress. Activation of NLRP3 after psychological stress has been associated with depression-like behaviors [15,47-49]. For example, NLRP3 in the brain was increased by treatments that can increase depression-like behaviors, including inescapable tail shocks [50] and by chronic unpredictable mild stress, which was blocked by treatment with the antidepressant fluoxetine [51].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of overt inflammation in the central nervous system (CNS), stress is capable of activating inflammatory signaling pathways via release of danger/damage-associated molecular patterns (DAMPs) and microbe-associated molecular patterns (MAMPs) that bind to immune receptors, a process termed “sterile inflammation” (Fleshner 2013, Slavich and Irwin 2014). High mobility group box 1 (HMGB1), one of the best-characterized DAMPs, resides undetected in the nucleus of a cell when unstimulated but is released upon activation as demonstrated in a rodent model of inescapable footshock stress (Cheng, Pardo et al 2016). The released HMGB1 protein can signal through toll-like receptors (TLRs) present primarily on microglia to activate these cells and further promote the spread of inflammation in the brain via NFκB signaling (Weber, Frank et al 2015, Cheng, Pardo et al 2016).…”
Section: Traversing the Blood Brain Barrier: From Peripheral Resismentioning
confidence: 99%
“…HMGB1 is a central player in the inflammatory network because it can be induced by a number of cytokines, and itself induces a series of inflammatory reactions [3]. The activation of both RAGE and TLR4 can induce neuroinflammation, contributing to the development of neurodegenerative diseases [4,5,6]. Neuroinflammation has also been associated with the induction of cerebral vasoconstriction following subarachnoid hemorrhage (SAH) [7,8,9].…”
Section: Introductionmentioning
confidence: 99%